2000
DOI: 10.1159/000051947
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy in Switzerland: A Prospective Audit of 2,179 Cases

Abstract: Background/Aims: Since its introduction in 1983, laparoscopic appendectomy (LA) has not replaced the conventional open procedure. The patient benefit seems limited to a decreased wound infection rate, and the overall morbidity and mortality rates remain equal to those of open appendectomy. Methods: The data (collected by the Swiss Association of Laparoscopic and Thoracoscopic Surgery) from 2,179 patients undergoing LA at 84 surgical institutions in Switzerland between January 1995 and December 1997 were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…Since Semm performed the first laparoscopic appendicectomy, numerous studies have shown conflicting results regarding the clinical benefit of this procedure. Most studies in recent years comprise between 50 and 150 patients [5][6][7][8][9], and only a minority have compared 200 or more [10][11][12]. Most of these studies are primarily designed to compare postoperative activity and time course for convalescence.…”
Section: Discussionmentioning
confidence: 99%
“…Since Semm performed the first laparoscopic appendicectomy, numerous studies have shown conflicting results regarding the clinical benefit of this procedure. Most studies in recent years comprise between 50 and 150 patients [5][6][7][8][9], and only a minority have compared 200 or more [10][11][12]. Most of these studies are primarily designed to compare postoperative activity and time course for convalescence.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of laparoscopic linear staplers, it became ''en vogue'' to apply these in LA, particularly for difficult cases such as perforation at the appendiceal base [4,5,11]. Currently, some authors advise the routine use of linear staplers during LA to avoid leakage from the appendiceal stump [24].…”
mentioning
confidence: 99%
“…after appendectomy or segmental colon resection) complete retrieval bags such as the lap-sac or the endo-catch systems can be used [11]. These systems offer a convenient handling of the resected specimen without the risk of any further contamination if the specimen is accidentally opened during retrieval.…”
Section: Retrieval Systemsmentioning
confidence: 99%
“…To date all open procedures for benign as well as malignant colon diseases have also been performed laparoscopically or laparoscopically assisted [1, 2, 3, 4, 5, 6, 7, 8]. The most frequent procedures described in the literature are ileocecal resection, left or right hemicolectomy [4, 9, 10, 11], sigmoid resection [2, 5]and colectomy with ileoanal anastomosis [12]. Low anterior rectum resection and abdomino-perineal rectum excisions are described less frequently [13].…”
Section: Introductionmentioning
confidence: 99%